The Sines industrial complex monitoring programme: a preliminary report - Jones, M P; Catarino, F M (Environmental Monitoring …, 1981)
It is anticipated that the establishment of the industrial complex at Sines, Alentejo, Portugal, will have some impact on the environment. Details of the methods used in the monitoring programme are provided. Records of the epiphytic lichen vegetation in permanent quadrats have been made and changes shown in selected sites over a three year period are discussed. Material has been collected for analysis for heavy metals and the results discussed. There is considerable variation in replicates and in interspecies values. The problem of age and bio-accumulation is mentioned. Scanning electron microscopy has shown the accumulation of particulates, as yet unidentified, the quantity varying with increase in age and surface texture. A broadly based study of the local epiphytic flora is being carried out to record the present day diversity. There appears, as yet, to be no detectable influence of the industrial complex on the epiphytic flora of the permanent quadrats.
Keywords: bio-accumulation; epiphytic lichens; Monitoring programmes (voyant); Sines industrial complex